2020
DOI: 10.7759/cureus.8144
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: Knowledge and Perceptions of the Public and Healthcare Professionals

Abstract: Background and objective The recent pandemic due to the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a major concern for the people and governments across the world due to its impact on individuals as well as on public health. The infectiousness and the quick spread across the world make it an important event in everyone's life, often evoking fear. Our study aims at assessing the overall knowledge and perceptions, and identifying the trusted sources of information for both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
105
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 9 publications
20
105
1
2
Order By: Relevance
“…Additionally, since they directly deal with the possible or confirmed cases, hence are most vulnerable to getting infected themselves and consequently, may become a source of transmission to thousands of the uninfected population. Therefore, the burden would be immense if a healthcare provider contracts the disease, making it highly necessary for them to be sufficiently prepared ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, since they directly deal with the possible or confirmed cases, hence are most vulnerable to getting infected themselves and consequently, may become a source of transmission to thousands of the uninfected population. Therefore, the burden would be immense if a healthcare provider contracts the disease, making it highly necessary for them to be sufficiently prepared ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…23,[31][32][33][34] The emergence of the COVID-19 pandemic has increased the health-care providers' need of information and information-seeking behavior drastically. 15,[35][36][37] Even though there are limited studies conducted on the informationseeking behavior in other domains, 10,11,38 the study conducted on health professionals' information seeking on the COVID-19 pandemic in the case of low-resource setting teaching hospitals is limited. Therefore, the aim of this study was to answer this evidence gap by assessing the information-seeking practice of the care providers.…”
Section: Introductionmentioning
confidence: 99%
“…Henceforth the mean difference was found to be signi icant (p=0.000). A similar study concluded that training program, workshops on COVID-19 was found signi icant among intense students (P=0.00) (Modi et al, 2020;Parikh and Bvsgpa, 2020).…”
Section: Resultsmentioning
confidence: 65%